The Influence of mathematics learning interest on the conceptual understanding of eighth-grade middle school students - Hilma Adzki Hidayati; Dadang Rahman Munandar (Universitas Sarjanawiyata Tamansiswa, 2023)
This study aims to determine the effect of interest in learning mathematics on the understanding of mathematical concepts in grade VIII junior high school students in the matter of number patterns. Number pattern material is one of the materials contained in the 2013 curriculum for class VIII which is expected to be mastered by students and students because it is closely related to everyday life. In this study the population was all class VIII students of SMP Negeri 28 Tangerang for the Academic Year 2022/2023. The sample selection was carried out in this study by means of probability random sampling, namely class VIII-D students as many as 36 students. The approach used in this research is quantitative and analyzed by simple linear regression. The technique of collecting data by providing non-test instruments in the form of questionnaires on students' interest in learning mathematics and test instruments on the subject of number patterns to measure understanding of mathematical concepts that are closely related to everyday life. Hypothesis testing is done by simple regression with prerequisite analysis, namely testing the normality of the data and the linearity of the data. The results showed that there is no significant effect of interest in learning on understanding mathematical concepts with the regression equation . So it can be concluded that interest in learning affects students' ability to understand mathematical concepts in an insignificant way.